The Association of Southeast Asian Nations Cybersecurity Architecture: The Challenge of Collective Diplomacy in Facing Transnational Threats - Darmayadi , Andrias; Fauziansyah Moenardy, Dwi; Budi Santoso, Rizal; Trisna Ramahadi, Bayu (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This study examines how the ASEAN cybersecurity framework addresses cross-border cyber threats. The focus is on how the system is built. How countries work together through Collective diplomacy, what major challenges they face and how they respond to threats in the region. A qualitative descriptive literature review was used in this study to achieve this aim. I used thematic analysis to analyze selected journals and selected sources from 2019 to 2024 based on relevance and quality. The ASEAN cybersecurity framework is managed through regulations such as the ASEAN Cybersecurity Cooperation Strategy. It focuses on technology development and information exchange. and cooperation with foreign groups. Collective diplomacy is implemented through multilateral forums and voluntary programs. However, this is often limited by the principle of national sovereignty. Key challenges include gaps in technical capabilities. Since each country has different laws for security purposes, there is a lack of trust and geopolitical issues. The system works well. But this is not very effective in real work. Because there is a difference between what is promised and what is fulfilled. However, the ASEAN cybersecurity framework sets out rules that must be adhered to. But the limitations of Collective diplomacy generally make it difficult to respond to rapidly changing international threats. Future research should explore different policy models and simulations. Help increase regional resilience.